Evaluating The Impact of Built-in Digital Spellcheckers on EFL Students’ Spelling Accuracy: A Case Study of First-Year Undergraduates at the University of Souk Ahras - Khouloud Bouguerche (My University, 2026)
Abstract This study investigates the impact of built-in digital spellcheckers on the spelling accuracy of first-year EFL students at the University of Souk Ahras. It examines whether these tools improve spelling performance and explores students’ perceptions of their usefulness and limitations. The study adopted a mixed-methods quasi-experimental design involving sixteen students. Data were collected through a pre-test, post-test, and a focus group interview. Students’ writing was analysed according to orthographic, morphological, capitalization, and typographical errors. Findings revealed a significant reduction in errors from 171 in the pre-test to 72 in the post-test (57.89%). Orthographic errors showed the greatest improvement, decreasing by 96.97%, while morphological errors remained comparatively persistent. Focus group findings showed that students perceived spellcheckers as useful for improving spelling accuracy, increasing error awareness, and supporting writing fluency, though concerns about overreliance were also raised. The study concludes that built-in digital spellcheckers can positively support spelling accuracy, particularly for surface-level errors, when used reflectively and alongside instructional support. -------------------- الملخص تهدف هذه الدراسة إلى بحث أثر المدققات الإملائية الرقمية المدمجة على الدقة الإملائية لدى طلبة السنة الأولى تخصص الإنجليزية بجامعة سوق أهراس، كما تستكشف تصورات الطلبة حول فوائد هذه الأدوات وحدودها .اعتمدت الدراسة المنهج المختلط شبه التجريبي بمشاركة ستة عشر طالبًا، وتم جمع البيانات من خلال اختبار قبلي واختبار بعدي ومقابلة مجموعة بؤرية. تم تحليل الكتابات وفق أخطاء إملائية شكلية وصرفية وأخطاء الحروف الكبيرة والأخطاء الطباعية. أظهرت النتائج انخفاضًا ملحوظًا في الأخطاء من 171 إلى 72 بنسبة 57.89٪، كما سجلت الأخطاء الإملائية الشكلية أعلى نسبة تحسن بلغت 96.97٪، بينما ظلت الأخطاء الصرفية أكثر استمرارًا. وأظهرت النتائج النوعية أن الطلبة ينظرون إلى المدققات الإملائية كأدوات مفيدة لتحسين الإملاء وزيادة الوعي بالأخطاء ودعم الطلاقة في الكتابة، مع وجود مخاوف من الاعتماد المفرط عليها. وتخلص الدراسة إلى أن المدققات الإملائية المدمجة يمكن أن تدعم الدقة الإملائية إيجابيًا، خاصة في الأخطاء السطحية، إذا استُخدمت بشكل واعٍ إلى جانب التوجيه التعليمي. ------------------------- Résumé Cette étude examine l’impact des correcteurs orthographiques intégrés sur la précision orthographique des étudiants de première année EFL à l’Université de Souk Ahras. Elle vise à déterminer si ces outils améliorent la performance orthographique et à explorer les perceptions des étudiants concernant leur utilité et leurs limites. L’étude adopte une approche mixte quasi-expérimentale menée auprès de seize étudiants. Les données ont été recueillies par un pré-test, un post-test et un focus group. Les productions écrites ont été analysées selon quatre catégories d’erreurs : orthographiques, morphologiques, de capitalisation et typographiques. Les résultats montrent une réduction significative des erreurs de 171 à 72 (57,89 %). Les erreurs orthographiques ont enregistré la plus forte amélioration (96,97 %), tandis que les erreurs morphologiques sont restées plus persistantes. Les résultats qualitatifs montrent que les étudiants perçoivent ces outils comme utiles pour améliorer l’orthographe, développer la conscience des erreurs et soutenir la fluidité rédactionnelle, malgré des inquiétudes liées à la dépendance excessive. L’étude conclut que les correcteurs intégrés peuvent soutenir positivement la précision orthographique lorsqu’ils sont utilisés de manière réfléchie.
Keywords: built-in digital spellcheckers; spelling accuracy; EFL learners; mixed methods; المدققات الإملائية المدمجة، الدقة الإملائية، متعلمو الإنجليزية; correcteurs intégrés; précision orthographique; apprenants EFL; recherche mixte